2001
DOI: 10.1097/00006534-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Results with Furlow Palatoplasty in Management of Velopharyngeal Insufficiency

Abstract: A retrospective study was undertaken to assess speech outcomes in patients undergoing Furlow palatoplasty. Since 1994, the authors have used the position of the levator veli palatini musculature to determine type of surgical intervention recommended for the management of velopharyngeal insufficiency. Furlow palatoplasty has been used in patients with clinical evidence of sagittally oriented levator veli palatini musculature. Forty-eight patients who underwent a Furlow palatoplasty between June of 1994 and Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0
21

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 41 publications
2
81
0
21
Order By: Relevance
“…For this reason, the literature has advocated surgical techniques that allow adequate velopharyngeal closure in a condition more similar to the normal anatomical conditions, i.e. without altering the anatomy of the velopharyngeal sphincter, thus reducing the morbidity risks (8,16,17,18) . One procedure used for that purpose is intravelar veloplasty (7,19,20,21) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, the literature has advocated surgical techniques that allow adequate velopharyngeal closure in a condition more similar to the normal anatomical conditions, i.e. without altering the anatomy of the velopharyngeal sphincter, thus reducing the morbidity risks (8,16,17,18) . One procedure used for that purpose is intravelar veloplasty (7,19,20,21) .…”
Section: Introductionmentioning
confidence: 99%
“…Since this is a muscular repositioning procedure, intravelar veloplasty may be incorporated to conventional techniques already used for secondary palatoplasty. The main criterion to be considered to select individuals for intravelar veloplasty should be the anteriorized attachment of the palatal musculature and presence of small velopharyngeal gap (7,17,22) . Several studies demonstrated good speech outcomes in individuals with VPI submitted to intravelar veloplasty (8,16,17,18,20,21) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nos pacientes com fissura labiopalatina, a anatomia e a fisiologia do esfíncter velofaríngeo estão alteradas e o objetivo principal da cirurgia primária do palato é estabelecer condições anatômicas para a adequada função velofaríngea (4)(5)(6) . Entretanto, mesmo após a palatoplastia primária, alguns pacientes podem permanecer com a função velofaríngea inadequada e apresentar alterações de fala, tais como: hipernasalidade, emissão de ar nasal (audível ou não), fraca pressão intra-oral e distúrbios articulatórios compensatórios, que caracterizam a disfunção velofaríngea (DVF) (7)(8) .…”
Section: Introductionunclassified